An Investigation of a Highly Successful Team Environment: The Case of the Male French National Whitewater Slalom Single Canoe and Kayak Team - Cartwright, James A. (Université d'Ottawa / University of Ottawa, 2011)
To date, most of the research on group cohesion has focused on team sports, with little known about how this body of knowledge relates to individual sports. The case of the male French whitewater slalom canoe and kayak team was chosen because of the success of the team at World Championships and Olympic Games. The purpose of the present case study was to investigate how the coaches and athletes of this highly successful team worked together in training and competition within a highly competitive environment. Data were collected through in-depth interviews with six athletes and four coaches. Three themes, each containing numerous sub-themes, emerged from the analysis: (a) the nature of collaboration within the team environment, (b) coach leadership, and (c) the fragility of collaboration. The results of the present study have advanced our understanding of what collaboration within an individual sport team may look like. For a period of time, the leadership skills of the coaches, as well as their technical coaching expertise, and the willingness of the talented and driven athletes to work together, contributed significantly to a collaborative environment for this team. Then a change in the Olympic entry rules, the departure of an influential coach, and the inevitable change in the ages and experiences of the athletes themselves all combined to erode the foundation of that productive and collaborative environment.
Keywords: cohesion; collaboration; coach leadership; competition; whitewater canoe and kayak slalom